Is the temperature rising? : the uncertain science of global warming - Philander, S. George (Princeton, N.J. : Princeton University Press, 1998)
Examines the debate over the issue of global warming, describes some of the physical and chemical processes that make Earth a habitable planet, and discusses how the interplay among those processes determines Earth's response to various atmospheric disturbances.
Includes bibliographical references (p. [257]-258) and index.
Booklist.
Publisher's Weekly.
Wilson's Senior High School.
Adult
Keywords: Environmental sciences -- Philosophy; Global warming; Human ecology; Environmental sciences -- Philosophy; Global warming; Human ecology